2018
DOI: 10.1097/md.0000000000010263
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of sepsis-induced myocardial dysfunction and stress-induced cardiomyopathy in sepsis or septic shock

Abstract: While both sepsis-induced myocardial dysfunction (SIMD) and stress-induced cardiomyopathy (SICMP) are common in patients with sepsis, the pathogenesis of the 2 diseases is different, and they require different treatment strategies. Thus, we aimed to investigate risk factors and outcomes between the 2 diseases.This retrospective study enrolled patients diagnosed with sepsis or septic shock, admitted to intensive care unit via emergency department in Korea University Anam Hospital, and who underwent transthoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 34 publications
0
68
1
7
Order By: Relevance
“…While our definition of myocardial injury artificially lowered the observed rate by excluding cases within 24 h of ICU admission and after AKI development), we still observed significant association between TWA-MAP < 65 mmHg and myocardial injury. However, it is possible that a raised troponin value is present in the absence of myocardial injury [27], although raised troponin values have been tied with myocardial injury within the septic population [2831]. Our results of myocardial injury analysis should be interpreted with caution due to lack of universal troponin screening and diverse troponin tests employed among various U.S. Hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…While our definition of myocardial injury artificially lowered the observed rate by excluding cases within 24 h of ICU admission and after AKI development), we still observed significant association between TWA-MAP < 65 mmHg and myocardial injury. However, it is possible that a raised troponin value is present in the absence of myocardial injury [27], although raised troponin values have been tied with myocardial injury within the septic population [2831]. Our results of myocardial injury analysis should be interpreted with caution due to lack of universal troponin screening and diverse troponin tests employed among various U.S. Hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study has shown that sepsis-induced elevation in circulating histones was associated with cardiomyocyte damage, which resulted in elevated plasma cTnI levels (26). In addition, in patients with septic shock, cTnI levels were elevated and strongly correlated with cardiac dysfunction as evidenced by echocardiography (27). It was previously reported that there is a positive correlation between circulating histone levels and cTnI (12).…”
Section: Correlation Between Plasma Histone H4 Levels and Ctni And Ntmentioning
confidence: 96%
“…Вместе с тем появляется все больше оснований связывать прирост НУП В-типа при сепсисе с гемодинамическим нарушениями и различными проявлениями миокардиальной дисфункции [31]. Взгляд на вероятность последней при сепсисе за последние годы претерпел существенные изменения.…”
Section: Discussionunclassified